Gi/o-Protein Coupled Receptors in the Aging Brain - de Oliveira, Patrícia G.; Ramos, Marta L. S.; Amaro, António J.; Dias, Roberto A.; Vieira, Sandra I. (Frontiers in Aging Neuroscience, 2019)
Cells translate extracellular signals to regulate processes such as differentiation, metabolism and proliferation, via transmembranar receptors. G Protein-Coupled Receptors (GPCRs) belong to the largest family of transmembrane receptors, with over 800 members in the human species. Given the variety of key physiological functions regulated by GPCRs, these are main targets of existing drugs. During normal aging, alterations in the expression and activity of GPCRs have been observed. The central nervous system (CNS) is particularly affected by these alterations, which results in decreased brain functions, neuroregeneration, and increased vulnerability to neuropathologies, such as Alzheimer’s and Parkinson diseases. GPCRs signal via heterotrimeric G proteins, as Go, the most abundant heterotrimeric G protein in CNS. We here review age-induced effects of GPCRs signaling via the Gi/o subfamily at the CNS. During the aging process, a reduction in protein density is observed for almost half of the Gi/o-coupled GPCRs, particularly in age-vulnerable regions such as the frontal cortex, hippocampus, substantia nigra and striatum. Gi/o levels also tend to decrease with aging, particularly in regions such as the frontal cortex. Alterations in the expression and activity of GPCRs and coupled G proteins result from altered proteostasis, peroxidation of membranar lipids and age-associated neuronal degeneration and death, and have impact on aging hallmarks and age-related neuropathologies. Further, due to oligomerization of GPCRs at the membrane and their cooperative signaling, down-regulation of a specific Gi/o-coupled GPCR may affect signaling and drug targeting of other types/subtypes of GPCRs with which it dimerizes. Gi/o-coupled GPCRs receptorsomes are thus the focus of more effective therapeutic drugs aiming to prevent or revert the decline in brain functions and increased risk of neuropathologies at advanced ages.